Success Rate of Vaginal Birth after Cesarean Delivery at Maharaj Nakorn Chiang Mai Hospital - Tongsong T. (2014)
Objective: To study the success rate of vaginal birth after cesarean delivery (VBAC) in pregnant women with prior cesarean scar who delivered at Maharaj Nakorn Chiang Mai Hospital. Study Design: Prospective descriptive study. Setting: Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand. Subject: One hundred and seventy-seven pregnant women with one or two prior cesarean deliveries, who attended the antenatal clinic and delivered at Maharaj Nakorn Chiang Mai Hospital between January, 2000 and September, 2002 were recruited with written informed consents. Intervention: Systematic non-directive counseling concerning VBAC compared with elective repeated cesarean delivery was given to the pregnant women. Couples freely chose their preferred route of delivery and were informed that they could change their mind at anytime. Subjects attended the high risk antenatal care clinic. Patients who requested repeated cesarean deliveries were scheduled for the operation at 38 weeks of gestation. All VBAC patients were admitted to the labor unit when in labor and were closely monitored. Labor and postpartum information was prospectively recorded. Main Outcome Measure: Success rate of VBAC. Result: Of 177 counselled women, 118 chose VBAC, 54 chose repeated cesarean and 5 could not make a decision. Thirty-three of the 177 cases were excluded, leaving 98 in the VBAC group and 46 in the repeated cesarean group. Baseline characteristics of the patients in both groups were not significantly different. Nineteen of the 98 cases were delivered by cesarean section because of obstetric indications (12/19) and changed their minds during the antenatal period (7/19). Forty-three of 79 cases had successful vaginal delivery, and 36 underwent repeated cesarean deliveries due to obstetric indications (19/36) and changed their minds during labor (17/36). The success rate of VBAC after trial of labor was 54.4 per cent (43 in 79). No uterine rupture or serious complication occurred in the present study. Conclusion: The attitude for VBAC was 66.7 per cent and the success rate of VBAC after trial of labor was 54.4 per cent in the present series. Several cesarean deliveries could be avoided by the VBAC policy. Unlike other previous reports, the failure rate of VBAC was rather high. This was associated with many factors such as change of mind due to labor pain.